2015
DOI: 10.5489/cuaj.3192
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prognostic factors affecting mortality in Fournier’s gangrene: A study of 72 cases

Abstract: Introduction: Fournier's gangrene is a rapidly progressing necrotizing fasciitis of the perineum and genital area associated with a high mortality rate. We presented our experience in managing this entity and identified prognostic factors affecting mortality. Methods: We carried out a retrospective study of 72 patients treated for Fournier's gangrene at our institution between January 2005 and December 2014. Patients were divided into survivors and nonsurvivors and potential prognostic factors were analyzed. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 33 publications
2
32
0
5
Order By: Relevance
“…[7,10,25] Corcoran et al [7] found an inpatient mortality rate of 10%, with a significant difference in FGSI scores between survivors and non-survivors (5.3 in survivors vs. 10.9 in non-survivors, p=0.002). In a recent study, Tarchouli et al, [25] reported that this index was a simple, reliable and valuable method for predicting disease severity and patient survival. However, the study by Tuncel et al [11] on 20 men with FG found no association between FGSI scores and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[7,10,25] Corcoran et al [7] found an inpatient mortality rate of 10%, with a significant difference in FGSI scores between survivors and non-survivors (5.3 in survivors vs. 10.9 in non-survivors, p=0.002). In a recent study, Tarchouli et al, [25] reported that this index was a simple, reliable and valuable method for predicting disease severity and patient survival. However, the study by Tuncel et al [11] on 20 men with FG found no association between FGSI scores and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Experience is an additional important factor affecting mortality in the treatment of patients with Fournier's gangrene: seeing more than 1 patient per year had an adjusted 42-84% lower mortality rate (p < 0.0001) [15,16]. Another key point for improving patient outcome is the immediate start of treatment with a broad antibiotic [2,18] and intensive care therapy [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Once considered to be the result of streptococcal infection alone, Fournier's gangrene is now understood to be polymicrobial in nature 13,14 and is typically caused by the opportunistic invasion of commensal bacteria. Commonly found organisms include Staphylococcus aureus, Streptococcus species, Escherichia coli and Acinetobacter.…”
Section: Alcoholismmentioning
confidence: 99%
“…Commonly found organisms include Staphylococcus aureus, Streptococcus species, Escherichia coli and Acinetobacter. 6,8,13 In this regard, antibiotic resistance may be a growing concern in Fournier's gangrene with methicillin-resistant Staphylococcus aureus (MRSA) being the most commonly cultured resistant organism. 15 Patients with multiple drug resistant organisms have shown a trend towards having poorer outcomes.…”
Section: Alcoholismmentioning
confidence: 99%